IMPLEMENTASI SISTEM SELF ASSESSMENT PADA PAJAK BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN (BPHTB) DI KABUPATEN BOYOLALI - Kartika Cahyaningtyas; Nafi’uddin Fauzi Mahfudh; Muh. Isra Bil Ali (Jurnal Akuntansi dan Pajak, 2025)
This study aims to determine the authority of the Land Deed Official (PPAT) in Boyolali Regency, Implementation of the self-assessment system based on Regional Regulations Regional Regulation Number 2 of 2011 concerning Land and Building Acquisition Fees in conjunction with Regional Regulation Number 12 of 2020 concerning Amendments to the Regulations on Land and Building Acquisition Fees. This type of research is empirical legal research, taking the research location in Boyolali Regency. The research sample was 6 Land Deed Officials (PPAT)/Notaries and 6 Temporary Land Deed Officials (PPATS)/Sub-district Heads. Data collection was carried out through field studies and literature studies to obtain primary and secondary data. Data analysis used interactive analysis methods. The results of this study can be presented that the role of the Land Deed Official (PPAT)/Notary in determining the Land and Building Acquisition Fee (BPHTB) tax is not in accordance with their duties. This is because there is still authority from the Land Deed Official (PPAT)/Notary that is not in accordance with its portion. In addition, there must also be coordination with the Regional Finance Agency (BKD) of Boyolali Regency and the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency of Boyolali Regency to provide guidance to Land Deed Making Officials (PPAT)/Notaries and Temporary Land Deed Making Officials (PPATS)/Sub-district Heads and the surrounding community. The self-assessment system which is used as the basis for data obtained from Regional Regulation Regional Regulation Number 2 of 2011 concerning Land and Building Acquisition Fees in conjunction with Regional Regulation Number 12 of 2020 concerning Amendments to the Regulation on Land and Building Acquisition Fees is still not in accordance with these regulations. Keywords: Tax, Self-assessment system, Land and Building Acquisition Fee (BPHTB)